SCHOLAR-ARCHEOLOGIST, EDUCATOR AND INDIVIDUAL (to the 80-th birthday anniversary of M.G. Gadzhiev) - Davudov, O M; Gasanov, M R; Gmyra, L B (History, Archeology and Ethnography of the Caucasus, 2015)
-